Massive Congenital Bidirectional Coronary Arteriovenous Malformation Presenting with Signs and Symptoms of Congestive Heart Failure in an Adult: A Case Report and Review of the Literature - H. M. M. Al Hashimi; A. J. Wardeh; S. Bulut; F. W. A. Verheugt (Case Reports in Cardiology)
Congenital anomalies of the coronary arteries are relatively rare. Mostly asymptomatic, however, some can cause problems, as heart failure, myocardial ischemia, and ventricular arrhythmia, and are associated with risk of complications, such as endocarditis and coronary rupture or sudden death. A case of a 69-year-old man with complaints of tiredness, dyspnea, and palpitation due to coronary artery fistula is presented with a review of the literature.